Improving the performance of a communication via diffusion system considering molecule degradation in nanonetworking - Kılıç, Fatma Nur. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
The interconnection between the nanoscale circuit components, which is referred to as nanonetworking, is a hot topic for nearly a decade. Among the various approaches studied in the literature, we apply communication via di usion (CvD) method. Despite its practicality and ease of implementation, CvD brings along its own drawbacks especially to the reliability of the system. In order to overcome these drawbacks, we consider molecule degradation, which the literature on molecular communication mostly overlooks, in this thesis. We evaluate the performance of this proposed model by simulations and by using analytical expressions. In the simulations, we demonstrate the positive e ects of molecule degradation on basic communication metrics in this scale. In addition, we use the analytical formulas in selecting the proper values of degradation utilized system parameters for mitigating intersymbol interference and correctly demodulating the signal. In this sense, the number of stray molecules remaining in the inter-cellular environment from the previous symbol is limited not to exceed the prede ned threshold value while the number of received molecules is bounded to be greater than it. In the subsequent analysis, we examine the e ects on the data rate and the energy consumption of the overall system. Results demonstrate that the increase in the data rate and the decrease in the energy expenditure can be achieved using appropriate half-life values.
Keywords: Nanonetworks.; Molecular communication (Telecommunication)